Survivability using traffic balancing and backup resource reservation in multi‐domain optical networks. (15th August 2018) - Batham, Deepak; Yadav, Dharmendra Singh; Prakash, Shashi
Summary: Survivability in the geographically distributed backbone multi‐domain optical networks (MDONs) is critical because of issues related to its size, usage of resources, and domain management policies of the comprising domains. In MDONs, the emerging scheduled traffic is increasingly multivendor, multimedia, and periodic. It is high during the office (working) hours and low during the non‐office (non‐working) hours in a day. A connection failure during the office hours may result in huge amount of information being lost. Towards providing an acceptable level of service even when a connection fails, we first provide traffic balancing (TB) based solutions where the intra/inter‐domain traffic is slided (S1‐TB), shifted (S2‐TB), or slided as well as shifted (S3‐TB) based on the service level agreement between the client and domain service provider. Of the above solutions, the solution based on sliding as well as shifting (S3‐TB) performs best, and hence for further improvement in S3‐TB, we incorporate backup multiplexing with advance backup resource reservation (BRR) and evaluate the performance of the strategy and report results. The performance evaluation of the above strategies is compared with the existing extended path shared protection (EPSP) by a simulator developed in MATLAB and tested on three‐domain and five‐domain standard network topologies, on the metrics of blocking probability, network resource utilization ratio, network capacity utilized by backup route, wavelength link used per backup lightpath, and a newly introduced metric, network resource utilization index. As compared with the existing strategy EPSP, the S3‐TB and S3‐TB with BRR showed improved performance on all the metrics. Abstract : In multi‐domain optical networks, the emerging scheduled traffic is increasingly multivendor, multimedia, and periodic. This traffic is irregular; high and low during the office and non‐office hours, respectively. The connection failure during the office hours results huge amount of information being lost. We proposed survivable solutions using traffic balancing where, the traffic is slided within or shifted beyond the time zone they actually arrived to reduce the traffic unevenness, and introduces the concept of backup resource reservation to achieve efficient network resource utilization.